Invasive crayfish (Procambarus clarkii, Girard, 1852) in a managed brackish wetland (Sardinia, Italy): Controlling factors and effects on sedimentary organic matter. (31st December 2019) - Palmas, F.; Podda, C.; Frau, G.; Cau, Al.; Moccia, D.; Peddio, S.; Solari, P.; Pusceddu, A.; Sabatini, A.
Abstract: The red swamp crayfish, Procambarus clarkii is among the most invasive aquatic species worldwide. Here we investigate the potential relationships between crayfish occurrence and a series of abiotic factors, as well as the effects of crayfish abundance on sedimentary organic matter (OM) quantity and degradation. A total of 329 sampling points was investigated in a managed protected brackish wetland (Southern Sardinia, Italy). A generalized additive model (GAM) was applied to investigate the influence of abiotic variables on the crayfish occurrence. We then assessed the potential effects of crayfish abundance on sedimentary OM quantity, biochemical composition and degradation rates. We report here that the occurrence of crayfish was mostly explained by the joint effects of water salinity, characteristics of soil's bank and bottom substrate composition. We report also that the presence of this crayfish, due to its bioturbation ability, is associated with a more homogeneous vertical distribution of OM along the sediment profile. Moreover, we revealed that the presence of P. clarkii is associated with OM contents and caloric contents that are significantly lower than those in crayfish-free sediments. These results suggest that the presence of P. clarkii determines not only a decrease in the quantity of food potentially available for the benthos, but also a decrease in its nutritional value. Moreover, we report also that the presence of P. clarkii is associated with a decrease in protein degradation rates and an increase in their turnover time, indicating that this species could have severe effects on the local C cycle. Highlights: Water salinity, soil and bottom substrate features' influenced crayfish occurrence. Their bioturbation ability homogenizes the organic matter distribution in sediments. P. clarkii presence decreases the quantity and quality of food available for benthos. P. clarkii presence could have severe effects on the local C cycle.